Train Ticket Inspection and Validation Using Biometrics - M.Gowthami, Ms; P.Karthikeyan, Mr; Kishore, P; Arun Aravinth, R (International Journal of Engineering and Technology, 2018)
The current suburban railway system comprises of some challenges, that is the tickets has to be checked manually and the population travelling through train have also increased immensely. This resulted in various issues such as never ending queues, wastage of paper, lots of resources and staff utilization and this is the Existing system. In the Proposed system, if the user intends to travel from a source to destination with no intention to return on the very same day, then only half ticket costing will be taken into consideration. Modification Part of the Project is our Implementation, Android User books the Outstation Ticket by specifying Source & destination with number of Tickets using Aadhaar Card. QR Code is generated comprising all of the above. Once User gets into train, user has to give Finger Print & Scan QR Code to take up their seat. The seat of passengers who hasnâ€™t arrived is dynamically allocated to Waiting list. All the information are transferred to TTR.Â Â